Endothelial committed oral stem cells as modelling in the relationship between periodontal and cardiovascular disease. Issue 10 (30th March 2018) - Pizzicannella, Jacopo; Diomede, Francesca; Merciaro, Ilaria; Caputi, Sergio; Tartaro, Armando; Guarnieri, Simone; Trubiani, Oriana
Abstract : In the present study we have mimicked, in vitro, an inflammatory process using Lipopolysaccharide derived from Porphyromonas Gingivalis (LPS‐G) and human Periodontal Ligament Stem Cells induced to endothelial differentiation (e‐hPDLSCs). The research project has been organized into the three following steps: i) induction of hPDLSCs toward endothelial differentiation; ii) evaluation of the molecular signaling pathway involved in the response to the LPS‐G, and iii) functional response evaluation of the living construct constituted by porcine decellularized valve/e‐hPDLSCs treated with LPS‐G. Obtained results showed that 5 μg/ml LPS‐G stimulus provokes: a slowdown of cell growth starting from 24 hr and the release of IL6, IL8, and MCP1 molecules. Signaling network analyzed showed the activation of TLR4/ NFkB/ERK1/2/p‐ERK1/2 signaling mediated by MyD88 in LPS‐G stimulated e‐hPDLSCs, moreover a time course put in evidence a nuclear traslocation of ERK1/2 and p‐ERK1/2 in differentiated samples. Following, the ability of e‐hPDLSCs to expand and colonize the decellularized porcine heart valves was appraised at ultrastructural level. Considering that, the Reactive Oxygen Species (ROS) play an important role in the progression and development of cardiovascular disease (CVD), in LPS‐G living construct model e‐hPDLSCs/decellularized porcine heart valves (dPHV), ROS production was assessed. Time lapse experiments evidenced that LPS‐G provokes in e‐hPDLSCs a rapid and sustained increase in ROS generation, negligible on undifferentiated cells. From obtained data, by multiparametric analyses, a reasonable conclusion may be that the inflammation process activated by LPS‐G can affect endothelial cells and could represent in vivo a possible pathological and predictor state of CVD. Abstract : The research project has been organized into the three following steps: i) induction of hPDLSCs toward endothelial differentiation; ii) evaluation of the molecular signaling pathway involved in the response to the LPS‐G, and iii) functional response evaluation of the living construct constituted by porcine decellularized valve/e‐hPDLSCs treated with LPS‐G. From obtained data, by multiparametric analyses, a reasonable conclusion may be that the inflammation process activated by LPS‐G can affect endothelial cells and could represent in vivo a possible pathological and predictor state of CVD.